2021
DOI: 10.1097/sla.0000000000005061
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease Outcomes After Vertical Sleeve Gastrectomy and Gastric Bypass

Abstract: Objective: The objective of this study is to assess whether vertical sleeve gastrectomy (VSG) increases the incidence of gastroesophageal reflux disease (GERD), esophagitis and Barrett esophagus (BE) relative to patients undergoing Roux-en-Y gastric bypass (RYGB) in patients with and without preoperative GERD. Summary of Background Data: Concerns for potentiation of GERD, supported by multiple high-quality retrospective studies, have hindered greater ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Some studies have reported alarming numbers of Barrett esophagus among patients with these complications, 25 whereas others have not. 26 Substance use disorder, treatment for depression and anxiety, and health care encounters for self-harm were all increased in the surgery group compared with the intensive lifestyle treatment group. These problematic side effects have been reported earlier after gastric surgery for duodenal ulcer 27 and later for RYGB.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have reported alarming numbers of Barrett esophagus among patients with these complications, 25 whereas others have not. 26 Substance use disorder, treatment for depression and anxiety, and health care encounters for self-harm were all increased in the surgery group compared with the intensive lifestyle treatment group. These problematic side effects have been reported earlier after gastric surgery for duodenal ulcer 27 and later for RYGB.…”
Section: Discussionmentioning
confidence: 95%
“…In all guidelines, a screening gastroscopy is recommended as a routine preoperative diagnostic test to assess Helicobacter pylori-and reflux esophagitis, the significant risk factor for Barrett's esophagus and esophageal cancer (38,39). However, the absolute necessity of this examination is still under debate and remains controversial (1,38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Tumor Screening Prior To Bariatric and Metabolic Surgerymentioning
confidence: 99%
“…While the incidence of reflux esophagitis after sleeve gastrectomy increases by about 30%, Y-Roux gastric bypass is the state-of-the-art bariatric and metabolic surgery against both obesity and reflux esophagitis (10,12,13,44,46). In addition, hiatal hernias, which are very common in patients with reflux esophagitis, can also be treated surgically simultaneously (8,(44)(45)(46)(47)(48)(49)(50).…”
Section: Tumor Screening Prior To Bariatric and Metabolic Surgerymentioning
confidence: 99%
See 2 more Smart Citations